2020
DOI: 10.1111/psyg.12530
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social network characteristics and depressive symptoms among older adults in the United States: differentiating between network structure and network function

Abstract: Background Social networks and social support can influence older adults' depressive symptoms, but depressive symptoms can also influence network maintenance. This study examined longitudinal relationships between social network structure, social support, and depressive symptoms. Methods Data are from Waves 1 (2005–2006) and 2 (2010–2011) of the National Social Life, Health, and Aging Project, a longitudinal study on health and social factors of older adults. Models examining: (i) the influence of T1 network s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…The first finding is in line with the importance of emotional support among older adults 19 and consistent with research showing that social support is protective against symptoms of psychological distress (e.g 26,27,29,31–34,39,40 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The first finding is in line with the importance of emotional support among older adults 19 and consistent with research showing that social support is protective against symptoms of psychological distress (e.g 26,27,29,31–34,39,40 …”
Section: Discussionsupporting
confidence: 86%
“…In the field of ageing research, there are reports of positive, negative and no effects of social support on symptoms of depression, 22–37 symptoms of anxiety 26,30,33,36–38 and combined symptoms of anxiety and of depression 39,40 …”
Section: Introductionmentioning
confidence: 99%
“…Considering that resilience is linked to depression or mental health, it is likely to be in line with previous studies suggesting a positive aspect of the number of contacts. The positive effect of frequent contact with social network members for older adults may be supported by previous literature, such that frequent contacts with social network members had a positive effect on mental health and frequent contacts with friends or relatives indirectly ameliorated depressive symptoms [ 26 , 41 ].…”
Section: Discussionsupporting
confidence: 63%
“…However, practical implications for protecting the social health of older adults living alone reported in previous studies are insufficient because the samples inadequately reflected the characteristics of older adults living alone. In addition, the result may be moderated by health issues, because the social network is connected to health issues, such as impaired cognitive function [ 24 , 25 ], physical disabilities [ 25 ], and depression [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review reported that social support is a determinant of healthy ageing and should be stimulated in general society by professionals in different fields (10) . According to researchers, the importance of social support increases in old age (10)(11)(12) and is a predictor of better levels of mental health (13) , absence of depression (14)(15) , absence of physical disability (16) , and of improvements in wellbeing and quality of life (17)(18) .…”
Section: Introductionmentioning
confidence: 99%